Workforce Demands of Rural Nurse Practitioners: A Descriptive Study - Jody Toerber-Clark; Marian Jamison; Monica Scheibmeir (Rural Nurse Organization; Binghamton University, 2021)
Purpose: Nurse practitioners (NPs) are rendering health care services in rural areas in increasing numbers, yet little is known about clinical skills and patient care management activities performed by these advanced practice nurses in the rural environment. The purpose of this descriptive study of rural NPs was to identify skills and patient care management activities that they have performed and considered critical to Kansas rural practice. Sample: A convenience sample of 208 nurse practitioners (NP) in rural and frontier Kansas were emailed a survey that asked about skills and activities they perform in their rural practice. Sixty-three responded for a response rate of 30%. Findings: The analysis produced a list of 26 skills and 37 patient care management activities critical to Kansas rural NP practice. Most of the skills/procedures were learned after graduation. Almost all the respondents reported additional training/certifications in advanced life support and trauma. The majority of respondents were family nurse practitioners who practiced in a variety of rural settings. "I grew up in a rural setting" and "Autonomy of practice" were the two top factors that influenced their decision to practice in a rural setting. Conclusion: The analysis produced a list of skills and patient care management activities critical to rural NP practice. Schools of nursing may find these lists useful as they prepare NPs for the rural workforce. Keywords: rural, nurse practitioner, training, education, skills, and patient care management activities DOI: https://doi.org/10.14574/ojrnhc.v21i1.656